Symbolic methods in control system analysis and design - Munro, N. (London, United Kingdom Institution of Engineering and Technology, 1999)
Symbolic computing has made a significant impact in the field, provides an up-to-date treatment of various issues in system modelling, analysis, design and synthesis methods. Coverage includes (i) the application of multidimensional Laplace transform to the modelling of nonlinear elements. (ii) a survey of customized computer algebra modelling programs for multibody dynamical systems. (iii) central results for the analysis and robust control of single-input single-output linear systems using a new linear programming approach. (iv) differential and real algebra for dealing with systems of polynomial equations and inequalities for nonlinear systems, and the computational aspects of algebraic and geometric invariants for both certain and uncertain systems. (v) the dynamic sliding mode approach to the robust control of both linear a nonlinear systems, and robust pole assignment for parametric uncertain linear systems. (vi) the development and testing of a new branch-and-bound algorithm for global optimisation, using symbolic algebra techniques. (vii) an overview and assessment of the use of symbolic computation program the analysis and design of control systems. The book will be of interest to postgraduate students and researchers in control engineering.
Also available in print version.
Electronic reproduction.
Keywords: Automatic control; System analysis; System design; Electronic books